First report of schulzia travassosi (nematoda, trichostrongylina, molineoidea) for amphibians of the Chaco region in Argentina and proposal of oswaldocruzia melanostictusi nov. comb. - Gonzalez, Cynthya Elizabeth (2015)
This is the first record of the nematode parasite Schulzia travassosi (Trichostrongylina, Molineidae) in two Argentinean amphibians, Leptodactylus bufonius and Rhinella major, collected in two localities of the Chaco region, Las Lomitas (Formosa Province) and Taco Pozo (Chaco Province). The species was observed using light and scanning electron microscopy (SEM) and compared with previous studies of Paraguayan specimens. Regarding metric characters, the measurements found in Argentinean specimens generally did not differ from those of Paraguayan specimens; some differences were observed in the total length of males and females (some longer and some shorter than Paraguayan specimens), length of the oesophagus (in almost all specimens shorter than in Paraguayan ones) and position of the vulva (nearer to posterior end in Argentinean specimens). The branches and sphincter of ovejector are slightly longer than in Paraguayan female specimens. In males, ray 4 is almost the same length as rays 2, 3 and 5, 6. Cephalic end, cephalic vesicle, synlophe and vulvar depression were viewed under SEM. Schulzia melanostictusi Chopra, Shing and Kumar, 1986 is reassigned as Oswaldocruzia melanostictusi (Chopra, Shing and Kumar, 1986) nov. comb.